2015
DOI: 10.5194/amt-8-1135-2015
|View full text |Cite
|
Sign up to set email alerts
|

Validation of GOME-2/MetOp-A total water vapour column using reference radiosonde data from the GRUAN network

Abstract: Abstract. The main goal of this paper is to validate the total water vapour column (TWVC) measured by the Global Ozone Monitoring Experiment-2 (GOME-2) satellite sensor and generated using the GOME Data Processor (GDP) retrieval algorithm developed by the German Aerospace Centre (DLR). For this purpose, spatially and temporally collocated TWVC data from highly accurate sounding measurements for the period January 2009-May 2014 at six sites are used. These balloon-borne data are provided by the GCOS Reference U… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 39 publications
12
20
1
Order By: Relevance
“…The range of these variations is about 15 %. This is similar to behaviour observed by (Antón et al, 2015). (Grossi et al, 2015) also reported residual cloud effects in comparisons with ECMWF ERA-Interim and combined SSM/I-MERIS data sets.…”
Section: Solar Zenith Angle Cloud Fraction and Surface Albedosupporting
confidence: 72%
See 3 more Smart Citations
“…The range of these variations is about 15 %. This is similar to behaviour observed by (Antón et al, 2015). (Grossi et al, 2015) also reported residual cloud effects in comparisons with ECMWF ERA-Interim and combined SSM/I-MERIS data sets.…”
Section: Solar Zenith Angle Cloud Fraction and Surface Albedosupporting
confidence: 72%
“…This is probably due to a larger fraction of data with smaller water vapour abundances being observed at large solar zenith angles. (Antón et al, 2015) observed similar behaviour while also reporting positive bias for cloud-free cases at solar zenith angles above 50 • . Large positive differences observed at low water vapour amounts (Fig.…”
Section: Solar Zenith Angle Cloud Fraction and Surface Albedosupporting
confidence: 65%
See 2 more Smart Citations
“…Although IWV from satellite measurements are validated using data from radiosonde [11,12] and ground-based instruments, such as GPS [13], microwave radiometer [14], and sun-photometer [15], it is difficult to find the strict matching pairs. Therefore, if the satellite-based IWV is compared with the validation data, spatial and temporal discrepancies may contribute heavily to the differences between them.…”
Section: Introductionmentioning
confidence: 99%